2019
DOI: 10.3390/agronomy9020109
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Sowing Date and Irrigation Strategy to Improve Maize Yield by Using CERES (Crop Estimation through Resource and Environment Synthesis)-Maize Model

Abstract: Summer maize (Zea mays L.) is a widely cultivated crop in the arid and semi-arid Guanzhong region of China. However, due to the spatial and temporal variation in rainfall, the seasonal maize yield varies substantially and occasionally is not economical for poor farmers to produce. Recent water-saving agricultural practices were developed by the government to make it possible to apply supplementary irrigation at optimum sowing dates to maximize maize production under limited rainfall in the region. CERES (Crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…Their results suggested that under future climatic conditions, potential crop reduction due to drought will be lower for wheat and higher for maize. Saddique et al [32] used the DSSAT model to simulate the impact of different irrigation decisions on summer maize yield. They found that irrigation during the heading and filling stages can result in maximum maize yield.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that under future climatic conditions, potential crop reduction due to drought will be lower for wheat and higher for maize. Saddique et al [32] used the DSSAT model to simulate the impact of different irrigation decisions on summer maize yield. They found that irrigation during the heading and filling stages can result in maximum maize yield.…”
Section: Introductionmentioning
confidence: 99%
“…FIGURE 9 | The response of optimal nitrogen application to planting density was simulated by DSSAT. The lower-right corner figure is the fitting analysis of the N application at the planting density was 9 plant m −2 , and the optimal N application amount is 246 kg ha −1 Saddique et al, 2019). Nevertheless, we still found some deficiencies in the model when we used it, as described below.…”
Section: Model Simulation and Applicationmentioning
confidence: 99%
“…These variables are frequently of a socio-economic nature when the assessment is at the scale of the farm [8]. In both cases, the proposed alternatives in the design of new systems aiming to improve the performance of those studied often have two important limitations: (i) the variables used to select alternative activities for the newly designed innovative systems are rarely multi-criteria (including production, biophysical, socio-economic criteria) [19] or multi-scale combining variables at the level of cropping systems (yield, organic matter, etc.) and variables at farm level (gross margin, labor, farm water consumption, etc.)…”
Section: What the Hpd Framework Brings To Farming System Redesignmentioning
confidence: 99%
“…and variables at farm level (gross margin, labor, farm water consumption, etc.) [8,17], and ii) the selection and feasibility of these alternatives are often limited to their agronomic and/or socio-economic performance without accounting for organizational constraints over time in line with the management of current activities [19,20]. HPD as applied here will allow us to overcome these two limits.…”
Section: What the Hpd Framework Brings To Farming System Redesignmentioning
confidence: 99%